UPAYA PENCEGAHAN GAMING DISORDER PADA REMAJA: LITERATURE REVIEW - Ika Juita Giyaningtyas; Armi Armi (Jurnal Cakrawala Keperawatan, 2024)
Background: Gaming disorder has become a global concern along with the increasing use of technology and video games among teenagers. The World Health Organization (WHO) designated gaming disorder as a mental health disorder in the International Classification of Diseases (ICD-11) in 2018. Gaming disorder is characterized by reduced control over games, as well as an increased priority of playing games compared to other activities. Based on this, it is necessary to make efforts to prevent gaming disorder, especially in adolescents. Purpose: This study discusses in more detail the prevention of gaming disorder in adolescents, so that the incidence of gaming disorder can be minimized as early as possible. Methods: The research carried out was secondary research with a literature review type. In selecting literature, researchers determine several articles' suitability. Based on keyword searches in 4 databases (Google Scholar, Science Direct, PubMed, and Springer Link), the total number of articles is 1,760 articles. Then the articles were selected based on the eligibility criteria into 6 articles. Results: The articles that have been reviewed discuss efforts to prevent gaming disorder in adolescents through telenursing, cognitive behavioral therapy, emotional regulation, and optimizing family functions. Conclusion: Prevention of gaming disorder in adolescents requires a holistic and integrated approach, with the important role of health workers and families.